Mathematics of interest rates and finance - Guthrie, Gary L.; Lemon, Larry D. (Upper Saddle River, NJ : Pearson Prentice Hall, 2010)
For courses in Actuarial Mathematics, Introduction to Insurance, and Personal/Business Finance. This text presents the basic core of information needed to understand the impact of interest rates on the world of investments, real estate, corporate planning, insurance, and securities transactions. The authors presuppose a working knowledge of basic algebra, arithmetic, and percents for the core of the book: their goal is for students to understand well those few underlying principles that play out in nearly every finance and interest problem. There are several sections that utilize calculus and one chapter that requires statistics. Using time line diagrams as important tools in analyzing money and interest exercises, the text contains a great deal of practical financial applications of interest theory as well as its foundational definitions and theorems. It relies on the use of calculator and computer technology instead of tables; this approach frees students to understand challenging topics without wilting under labor-intensive details.
&#x000A
Includes bibliographical references (p. 315-316) and index.
oif 10/07/14
Loan
Keywords: Finance -- Mathematical models; Interest rates -- Mathematical models; Investments -- Mathematical models